Racing car driveline design: carbon composite bonded half-shaft. (2016) - Evans, Jeremy; Bab-Hadiashar, Alireza; Watkins, Simon
In this paper the feasibility of incorporating a carbon fibre composite half-shaft into the final drive of an electric racing vehicle is studied. Carbon fibre composite tubing is bonded with aluminium inserts to achieve a low mass and high stiffness alternative to conventional half-shaft design. The drive line system was validated using a number of techniques including; finite element analysis (FEA) and torsional tensile testing. Testing revealed that the carbon fibre composite and aluminium half-shaft design presented in this study was 60% lighter and 2.5 times stiffer than conventional alloy steel half-shaft designs.